Penggunaan Wakamono Kotoba sebagai Interjeksi dalam Group Slack Kerja di B/C Asakusa Hotel : The Use of Wakamono Kotoba as Interjections in the Work Slack Group at B/C Asakusa Hotel - Muhammad Fikri haykal; Zahra Zahira (Undiksha Press, 2026)
This study aims to analyze the use of wakamono kotoba (Japanese youth slang) as interjections in digital communication, particularly in workplace conversations via the Slack platform at B/C Asakusa Hotel. The research employs a descriptive qualitative method with documentation and classification techniques based on five types of interjections: emotive, cognitive, interactive, evaluative, and phatic. The data were analyzed according to conversational context and the politeness maxim theory to assess their politeness functions. The findings reveal that interjections are used to express emotions, provide evaluations, and maintain social relationships among employees. Wakamono kotoba interjections undergo linguistic processes such as abbreviation, phonetic modification, and word lengthening as expressive reinforcement, reflecting the linguistic creativity of younger generations. The use of wakamono kotoba on Slack not only creates a more relaxed and inclusive work atmosphere but also strengthens solidarity and communication efficiency in a professional digital environment. Furthermore, the use of wakamono kotoba both adheres to and violates principles of linguistic politeness, thereby contributing to a more conducive workplace atmosphere.